EDUKASI BENTUK PERDAGANGAN MANUSIA DAN IMPLEMENTASI PROTOKOL PALERMO DI KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS - Alunaza, Hardi; Maryuni, Sri; Rusdiono; Pardi; Suwarso, Widha Anistya (Jurnal Abdi Insani, 2024)
Sambasi is known as the source and destination of human trafficking crimes. This is influenced because the number of people who work is not proportional comparing to the number of existing jobs. In addition, differences in economic levels ease of access to neighboring countries, weak administrative systems, and less valid information received about the job opportunities offered. In order to assist the government in dealing with these problems, the community service team took the initiative to disseminate community service activity. Through this activity, the team from faculty of social and political science, Tanjungpura University provided socialization related to forms of human trafficking, namely forms of human trafficking based on the purpose of delivery, based on the victim occured, and based of the exploitation. Including providing socialization and education related to the implementation of the Palermo Protocol as a response to the crime of human trafficking. This service activity is carried on July 2022 in the form of carrying out activities consisting of lectures on material delivery, socialization, and hearing discussions from the audiences. While the evaluation carried out in this activity is in the form of an analysis of a qualitative analysis. The result of this community service activity is that the community in Sajingan Besar District gains knowledge about forms of human trafficking, integrated handling of cases and victims, availability of services for recovery and reintegration, and law enforcement. The socialization and education provided by the service team can help the public understand the forms of protection against human trafficking crimes. The community also receives good education regarding victim identification, the recovery process, social rehabilitation and the reintegration process. The public obtains and has a good understanding of forms of human trafficking and the implementation of the Palermo protocol.